Predictors and clinical implication of high-sensitivity cardiac troponin-I elevation following diagnostic cardiac catheterisations. Issue 1 (9th April 2017) - Hamaya, Rikuta; Yonetsu, Taishi; Murai, Tadashi; Kanaji, Yoshihisa; Usui, Eisuke; Matsuda, Junji; Hoshino, Masahiro; Araki, Makoto; Hada, Masahiro; Niida, Takayuki; Ichijo, Sadamitsu; Kanno, Yoshinori; et al.
Abstract : Objectives: Although diagnostic coronary angiography (CAG) is performed worldwide, procedure-related myocardial necrosis (PMN) following diagnostic catheter-based procedures has not been well investigated. The aim of this study was to determine clinical and procedural factors associated with PMN, using a high-sensitivity cardiac troponin I (hs-cTnI) assay, and to investigate the clinical implications of PMN. Methods: Among 697 patients undergoing elective CAG and pre- and post-procedural hs-cTnI (pre-TnI, post-TnI, respectively) measurements, a total of 538 patients (124 female) were evaluated, with 2.2% lost during follow-up. Minor PMN was defined as post-TnI above the sex-specific upper reference limit (URL), with a 20% increase from the pre-TnI level. Major PMN was defined as post-TnI above 5x the URL. Clinical and procedural factors predicting PMN and the association between PMN and major adverse cardiac events (MACE) following CAG were examined. Results: PMN of any type was detected in 178 patients (33.0%), while major PMN was observed in 32 patients (5.9%). Female sex, estimated glomerular filtration rate, procedural time, left ventricular end-diastolic pressure (LVEDP) and fractional flow reserve measurement independently predicted any PMN; whereas, only LVEDP and log-transformed N-terminal pro-brain natriuretic peptide independently predicted major PMN. The incidence of MACE was significantly associated with major PMN. Cox proportional-hazards models revealed that major PMN, pre-TnI, and the absence of statin use were independently associated with MACE. Conclusions: Diagnostic cardiac catheteriation may highlight cardiomyocyte susceptibility to stress in patients with or without CAD. CAG-related major myocardial injury might be associated with future adverse cardiac events independently of the presence or absence of functional stenosis.